Extrapolation theorems for (p; q)-factorable operators - Rabia, Besma (Faculty of Mathematics and computer sciences Department of Mathematics - Option : Functional analysis, 2021)
In this research, we studied some classes of linear operators ideals such as the class of p-factorable operators, p-th power factorable operators, and the class of (p; q)-factorable operators. The main aim of our work is to present the ideal of Fp;q-factorable operators which introduced by Orlando GALDAMES-BRAVO. Some extrapolation theorems related to this class are shown.
Keywords: (p; q)- factorable operator, p-th power factorable operator, vector measure, p-summing operator.